2016
DOI: 10.1038/srep37460
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of TRPA1 inhibition by HC-030031 utilizing species-specific differences

Abstract: Pain is a harmful sensation that arises from noxious stimuli. Transient receptor potential ankyrin 1 (TRPA1) is one target for studying pain mechanisms. TRPA1 is activated by various stimuli such as noxious cold, pungent natural products and environmental irritants. Since TRPA1 is an attractive target for pain therapy, a few TRPA1 antagonists have been developed and some function as analgesic agents. The responses of TRPA1 to agonists and antagonists vary among species and these species differences have been u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 52 publications
(76 reference statements)
7
48
0
Order By: Relevance
“…Different organisms have been shown to have different sensitivities to the antagonistic effects of HC-030031. For example, divergence of a single amino acid (N855 in human TRPA1) in frog and zebrafish TRPA1 is responsible for their insensitivity to the inhibitor (52). Although the mechanism of TRPA1 inhibition by HC-030031 could not be resolved structurally (53), it has been suggested to cause a conformational change in TRPA1 which disrupts ligand binding (52).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different organisms have been shown to have different sensitivities to the antagonistic effects of HC-030031. For example, divergence of a single amino acid (N855 in human TRPA1) in frog and zebrafish TRPA1 is responsible for their insensitivity to the inhibitor (52). Although the mechanism of TRPA1 inhibition by HC-030031 could not be resolved structurally (53), it has been suggested to cause a conformational change in TRPA1 which disrupts ligand binding (52).…”
Section: Resultsmentioning
confidence: 99%
“…For example, divergence of a single amino acid (N855 in human TRPA1) in frog and zebrafish TRPA1 is responsible for their insensitivity to the inhibitor (52). Although the mechanism of TRPA1 inhibition by HC-030031 could not be resolved structurally (53), it has been suggested to cause a conformational change in TRPA1 which disrupts ligand binding (52). Thus, it is possible that in planarians HC-030031 may cause a different conformational change in TRPA1 to instead potentiate AITC activation.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular docking and site‐directed mutagenesis analyses in our study suggest that the hydrophobic pocket near Asn855 in the linker region between S4 and S5 is a putative binding site for saikosaponins. The hydrophobic pocket was previously suggested to be a binding site for an antagonist HC030031, and Asn855 was demonstrated to contribute significantly to HC030031 antagonism (Gupta et al, ). Interestingly, substitution of Asn855 by Ser in TRPA1 results in a gain‐of‐function mutation and is associated with enhanced secondary hyperalgesia to punctuate stimuli (Kremeyer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…To identify a putative binding site for saikosaponins in TRPA1, we retrieved binding pockets for known antagonists from published literature: (1) the vestibule region of the pore (Klement et al, ); (2) the vicinity of the selectivity filter region that was reported to be a binding site for A967079 (Paulsen et al, ); and (3) a hydrophobic pocket near Asn855 in the linker region between S4 and S5 that was reported to be a binding site for HC‐030031 (Gupta et al, ). Then, saikosaponins were subjected to molecular docking into each binding pocket in a crystallographic structure of human TRPA1 (PDB ID: 3J9P).…”
Section: Molecular Docking Studymentioning
confidence: 99%
See 1 more Smart Citation